Mechanistic aspects of the electrocatalytic oxidative cleavage of 1,2-diols by electrogenerated Pb(IV) - Marken, F; Squires, A; Alden, J; Compton, R; Buston, J; Moloney, M (1998)
The electrochemical oxidation of Pb(II) to Pb(IV) in acetonitrile solution containing benzoic acid and pyridine is possible at a basal-plane pyrolytic-graphite electrode and associated with a rapid ligand exchange at the metal center. The Pb(IV) species generated under these conditions is shown to react with diols such as 1,2:5,6-di-O-isopropylidene-D-mannitol, 1,2-ethanediol, cis- and trans-1,2-cyclopentanediol, which undergo a two-electron oxidation associated with carbon-carbon bond cleavage. Voltammetric data obtained by both channel flow cell and rotating disk electrode experiments are analyzed by numerical simulation. Consistent results for a second-order EC′ (electrocatalytic) reaction pathway were obtained. Voltammetric data obtained by systematically varying the concentration of pyridine and benzoic acid reveal a complex mechanism with a distinct trend in reaction rate for each diol expressed in terms of apparent fractional reaction orders when analyzed in terms of a chemically oversimplified EC′ mechanism. This behavior is given mechanistic significance by analysis of the data using numerical simulation employing the following "branched" ECrevCrevCirrev′ reaction scheme, which allows all the experimental results to be rationalized (benz = benzoic acid, py = pyridine): Pb(II) ⇄ Pb(IV) + 2e-; Pb(IV)(benz)h(py)i + diol ⇄ Pb(IV)(benz)h(diol)(py)i with rate constants k1 and k-1 for the forward and reverse reactions, respectively; Pb(IV)(benz)h+j(diol)(py)i-k + k(py) ⇄ Pb(IV)(benz)h(diol)(py)i + j(benz) with rate constants k2 and k-2 for the forward and reverse reactions, respectively; Pb(IV)(benz)h(diol)(py)i → Pb(II) + products with rate constant kf. Here, the chemical processes are associated with appropriate rate constants, kn, and the equilibrium constant of a process is given by Kn = kn/k-n (n = 1, 2). The "true" second-order rate constants K1kf obtained for the electrocatalytic cleavage of 1,2:5,6-di-O-isopropylidene-D-mannitol (k = j = 1), K1kf = (36 ± 7) × 103 M-1 s-1, 1,2-ethanediol (k = 1; j = 2), K1kf = (70 ± 14) × 103 M-1 s-1, trans-1,2-cyclopentanediol (k = 1; j = 0), K1kf = (180 ± 36) × 103 M-1 s-1, and cis-1,2-cyclopentanediol (k = j = 0), K1kf = (280 ± 56) × 103 M-1 s-1 are similar to within 1 order of magnitude. The effect of the diffusion of coexisting species coupled via fast preequilibria to the irreversible chemical process is discussed in respect to the physical meaning of the rate constants determined by applying a simplified mechanistic scheme.